Mito e história: o diálogo entre passado e futuro na constituição de identidade nacional em Iracema e Macunaíma - Silva, Sandra Mara Alves da (2020)
The present study is focused on the Works of Iracema (1865), by José de Alencar, and Macunaíma (1928), by Mário de Andrade. It is intended an analysis of the construction of the national identity, through the discussion of the making of a collective past of the brazilian people within such Works. We understand that each work is unique and its process of composition being also unique, but we also acknowledge similar aspects, as such as the settings of Comparative Literature, so from then the thorough observation of Composição Mitológica do Brasileiro in both novels. We understand that the said authors, through their Works, built up a mythical past common to the whole brazilian nation, able to instigate the feeling of belonging and sharing a common origin, building up this way an idea of national identity and offering then to brazilians as a whole the feeling as a way of integration of something bigger; a brotherhood laid upon the mythical collective national past. Before the analysis itself, we’ll seek to discuss the main concepts that ground and fundament our discussion, they being Culture, Identity, Myth and Collective Identity. Such concepts will be developed along the first chapter – based on reflections by Raymond Williams (1988), Castells (1999), Foucault (1978), e Candau (2012) – and the conclusions about that discussion will be brought up diluted among the analysis of the Works. On chapters two and three we’ll get to the observance of the Composição Mitológica do Brasileiro in Iracema and Macumaíma. We understand that both novels formulate a mythology for the origins o four people, laid upon fundamentally on the relations individual x nature and historical time x mythical time. From those relations, we believe that each author builds up one mythical single narrative, able to explain on an “irrealistic” form, despised of scientific concepts, the origin of the brazilian people and their cultural traditions. This origin, presented on the Works through the force of literature, is able to touch our people, this being able to acknowledge on the Works their ancestors; and this mythical common ancestrality common to all brazilians is the great responsible for the construction of our collective national identity.